Electrochemical device and electronic device comprising the same

By optimizing the mass percentage and cracking width of the positive electrode active material layer of the lithium-ion battery, and adding specific compounds to the electrolyte, the cracking problem of the lithium-ion battery coating is solved, and the performance and production efficiency of the battery are improved.

CN119447162AActive Publication Date: 2025-02-14NINGDE AMPEREX TECHNOLOGY LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411646563.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-02-14
Estimated Expiration
2041-09-30

AI Technical Summary

Technical Problem

In the process of increasing the weight of the positive electrode coating to increase the energy density, existing lithium-ion batteries are prone to coating cracking problems, which affects the consistency and electrochemical performance of the battery. The existing methods suppress cracking while increasing the manufacturing cost, making it difficult to Achieve mass production.

Method used

By controlling the mass percentage and cracking width of the positive electrode active material in the positive electrode active material layer, M/W ≥ 47.5 is ensured, and the compound with cyano group or compound with F-P-O bond is added to the electrolyte, the structure of the electrochemical device and composition.

Benefits of technology

It effectively suppresses the growth of DC internal resistance at high voltage and high temperatures, improves the floating charging performance at high voltages, improves the capacity retention rate, low temperature performance and cycling performance of the battery, reduces manufacturing costs, and realizes the possibility of mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447162A_ABST
    Figure CN119447162A_ABST
Patent Text Reader

Abstract

The invention relates to an electrochemical device and an electronic device comprising the same. The electrochemical device comprises a positive electrode, a negative electrode and an electrolyte, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, based on the mass of the positive electrode active material layer, the mass percentage of the positive electrode active material is M%, the value range of M is 95-99, the cracking width of the surface of the positive electrode active material layer is W mm, and M and W meet the condition that M / W is larger than or equal to 47.5. The electrochemical device provided by the invention has reduced DC internal resistance and improved capacity retention rate, low temperature performance and floating charge performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with application number 202180012340.4, application date September 30, 2021, and invention name “Electrochemical device and electronic device containing the same”. Technical Field

[0002] The present application relates to the field of energy storage, and in particular to an electrochemical device and an electronic device comprising the same, in particular a lithium-ion battery. Background Art

[0003] In recent years, with the continuous expansion of the scale of battery industrialization and the development of related technologies, the energy density of lithium-ion batteries has received more and more attention and challenges. In the work of continuously improving and enhancing energy density, the most effective solution is to increase the coating weight of the positive electrode and reduce the use of inactive materials. However, when the coating weight increases, due to the increase in stress, serious coating cracking problems will occur, affecting the consistency and electrochemical performance of the battery.

[0004] Although the prior art can reduce the coating speed, lower the oven temperature, and thus reduce the drying speed of the electrode, which can prevent the solvent in the electrode from evaporating too quickly and causing excessive stress and cracking of the electrode coating, this method inhibits industrial production, increases manufacturing costs, and is difficult to achieve mass production. Summary of the invention

[0005] The embodiments of the present application solve the problems existing in the prior art to some extent by providing an electrochemical device and an electronic device that can fully suppress the growth of DC internal resistance under high voltage and high temperature and effectively improve the floating charge performance under high voltage.

[0006] In one embodiment, the present application provides an electrochemical device, which includes a positive electrode, a negative electrode and an electrolyte, the positive electrode includes a positive electrode collector and a positive electrode active material layer located on the positive electrode collector, the positive electrode active material layer includes a positive electrode active material, wherein based on the mass of the positive electrode active material layer, the mass percentage of the positive electrode active material is M%, the value range of M is 95 to 99, and the crack width on the surface of the positive electrode active material layer is Wmm, wherein M and W satisfy: M / W≥47.5.

[0007] In some embodiments, W≤2.

[0008] In some embodiments, the mass per unit area of ​​the positive electrode active material layer is M1 mg / 1540.25 mm 2 , the value range of M1 is 100 to 400, where M1 and W satisfy: M1 / W≥50.

[0009] In some embodiments, the solid content of the positive electrode active material layer coating slurry is M2%, the value range of M2 is 55 to 80, wherein M2 and W satisfy: M2 / W≥27.5.

[0010] In some embodiments, the positive electrode includes a fluorine-based binder having a melting point in the range of 155°C to 270°C.

[0011] In some embodiments, the positive electrode active material layer includes a polymer compound having an ether bond, wherein based on the mass of the positive electrode active material layer, the mass percentage of the polymer compound having an ether bond is M4%, and M4≤0.3.

[0012] In some embodiments, the oxidation potential of the polymer compound having an ether bond is greater than or equal to 4.6V.

[0013] In some embodiments, the electrolyte includes an additive A, and the additive A includes at least one of a compound having a cyano group or a compound having a FPO bond.

[0014] In some embodiments, the mass percentage of the additive A is a %, and the value of a ranges from 0.1 to 15.

[0015] In some embodiments, M / a ≥ 6.33.

[0016] In some embodiments, the compound having a cyano group includes at least one of the following compounds: succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether , 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol di(2-cyanoethyl)ether, triethylene glycol di(2-cyanoethyl)ether, tetraethylene glycol di(2-cyanoethyl)ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl)ether, 1,4-dicyano-2-butene, 1 ,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexatriconitrile, 1,2,6-hexatriconitrile , 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane or 1,2,5-tris(cyanoethoxy)pentane.

[0017] In some embodiments, the compound having a FPO bond includes at least one of lithium difluorophosphate, a compound of Formula 1, a compound of Formula 2, a compound of Formula 3, or a compound of Formula 4: Formula 1, Formula 2: Formula 3, Formula 4.

[0018] In some embodiments, the positive electrode active material satisfies one of the following conditions:

[0019] (1) The positive electrode active material includes lithium iron phosphate, and the D50 of the positive electrode active material is D1µm, where 2×D1≥W;

[0020] (2) The positive electrode active material includes lithium manganese iron phosphate, and the D50 of the positive electrode active material is D2μm, where 5×D2≥W;

[0021] (3) The positive electrode active material includes lithium manganate, and the D50 of the positive electrode active material is D3µm, where 0.1×D3≥W;

[0022] (4) the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the D50 of the positive electrode active material is D4 μm, wherein 0.15×D4≥W; and

[0023] (5) The positive electrode active material includes lithium cobalt oxide, and D50 of the positive electrode active material is D5µm, where 0.15×D5≥W.

[0024] By selecting a suitable particle size, the present application can further adjust the flatness of the positive electrode surface, thereby improving the performance of the lithium-ion battery.

[0025] In some embodiments, the electrolyte further includes an additive B, and the additive B includes at least one of fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate, vinyl ethylene carbonate, or phosphoric acid cyclic anhydride.

[0026] In another embodiment, the present application provides an electronic device, which includes the electrochemical device according to the embodiment of the present application.

[0027] The electrochemical device provided in the present application has reduced DC internal resistance and improved capacity retention, low temperature performance and floating charge performance.

[0028] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0030] Figure 1 SEM images of the surface of the positive electrode active material layer in Examples 1-8 of the present application are shown. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0032] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0033] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0034] In the detailed description and claims, a list of items connected by the terms "one of," "one of," "a kind of," or other similar terms may mean any of the listed items. For example, if items A and B are listed, the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, the phrase "one of A, B, and C" means only A; only B; or only C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0035] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0036] 1. Electrochemical Device

[0037] In some embodiments, the present application provides an electrochemical device, which includes a positive electrode, a negative electrode, and an electrolyte.

[0038] positive electrode

[0039] 1. Positive electrode active material layer

[0040] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material layer may be one or more layers. In some embodiments, each layer of the multilayer positive electrode active material may contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly embed and deintercalate metal ions such as lithium ions. In some embodiments, the discharge capacity of the positive electrode active material is less than the chargeable capacity of the negative electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0041] (1) Crack width on the surface of the positive electrode active material layer

[0042] In some embodiments, based on the mass of the positive electrode active material layer, the mass percentage of the positive electrode active material is M%, and the value range of M is 95 to 99.

[0043] In some embodiments, M is 95, 96, 97, 98, 99 or a range consisting of any two of these values. When the mass percentage of the positive electrode active material in the positive electrode active material layer is higher than 95%, the energy density of the electrochemical device can be significantly improved.

[0044] In some embodiments, the crack width on the surface of the positive electrode active material layer is W mm, W≤2. In some embodiments, W is 0.01, 0.02, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.4, 1.5, 1.8, 2 or a range consisting of any two of these values. When the crack width on the surface of the positive electrode active material layer is infinitely small, especially when there is no crack, the floating charge performance of the electrochemical device under high voltage can be significantly improved.

[0045] In some embodiments, M and W satisfy: M / W ≥ 47.5. In some embodiments, M / W is 47.5, 50, 60, 80, 90, 100, 120, 150, 200, 300, 400, 500, 100, 1500, 1800, 2000, 5000, 8000, 9000, 10000, 15000, 18000, 20000, or a range consisting of any two of these values.

[0046] When the positive electrode satisfies the above relationship, it can not only improve the interface stability of the positive electrode active material layer, but also fully inhibit the growth of the DC internal resistance of the electrochemical device at room temperature and high temperature, and unexpectedly improve the floating charge performance under high voltage.

[0047] The crack width on the surface of the positive electrode active material layer can reflect the surface properties of the positive electrode active material layer, which is one of the parameters characterizing the positive electrode active material layer. The smaller the crack width, the better the interface flatness of the positive electrode active material layer, which can significantly improve the cycle performance, rate performance, floating performance of the electrochemical device and reduce the DC internal resistance of the electrochemical device. The crack width of the positive electrode active material layer can be affected by many factors, mainly including the coating weight of the positive electrode active material layer, the compaction density of the positive electrode active material layer, the solid content of the positive electrode active material layer coating slurry, the particle size of the positive electrode active material, the content of the positive electrode active material, the positive electrode active material layer binder, the positive electrode active material layer additive, the functional treatment layer on the surface of the positive electrode active material layer, and the porosity of the positive electrode active material layer.

[0048] The cracking in this application refers to cracks generated on the surface of the positive electrode active material layer due to internal stress, external impact or environmental conditions. The crack width on the surface of the positive electrode active material layer in this application refers to the largest crack width among all cracks, which can be measured by a ruler or other instruments for measuring size.

[0049] (2) Quality of the positive electrode active material layer

[0050] In some embodiments, the mass per unit area of ​​the positive electrode active material layer is M1 mg / 1540.25 mm 2 , M1 ranges from 100 to 400. In some embodiments, M1 is 100, 120, 140, 150, 160, 180, 200, 240, 250, 270, 280, 290, 300, 350, 380, 400 or a range consisting of any two of these values. When M1 ranges from 100 to 400, the positive electrode surface can maintain structural stability during the charge and discharge cycle, further improving the performance of the lithium-ion battery. If the value of M1 exceeds 400, the active layer is too thick, the permeability of the electrolyte is reduced, and the electron transmission in the battery will also be difficult, causing the battery polarization to increase, thereby causing the high current density charge and discharge characteristics to deteriorate. In addition, if the value of M1 is lower than 100, the active layer will have a greater impact on the current collector during processing, destroying the current collector interface, and the relative displacement between the active substances will also increase, affecting the performance.

[0051] In some embodiments, M1 and W satisfy: M1 / W≥50. In some embodiments, M1 and W satisfy: M1 / W is 50, 80, 100, 150, 200, 250, 300, 350, 400, 500 or a range consisting of any two of these values. When the positive electrode satisfies the above relationship, a further improved effect can be obtained.

[0052] (3) Solid content of positive electrode active material layer coating slurry

[0053] In some embodiments, the solid content of the positive electrode active material layer coating slurry is M2%, and the value range of M2 is 55 to 80. In some embodiments, M2 is 55, 58, 60, 63, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of these values. When the value range of M2 is 55 to 80, the positive electrode surface defects are less, further improving the performance of the lithium-ion battery. If it exceeds this range, the pole piece will crack severely during baking. In addition, if it is lower than this range, the solvent will be wasted and the baking time will be extended in the process of preparing the positive electrode active material layer, resulting in process losses.

[0054] In some embodiments, M2 and W satisfy: M2 / W≥27.5. In some embodiments, M2 / W is 27.5, 30, 32, 35, 38, 40, 45, 50, 60, 70, 80, 90, 100, 120, 200, 300, 350, 370, 400, 500, 600, 700, 800, 1000, 1100, 1400, 1500, 3000, 5000, 7000, 9000, 10000, 16000, 20000 or a range consisting of any two of these values. When the positive electrode satisfies the above relationship, a further improved effect can be obtained.

[0055] (4) Binder in the positive electrode active material layer

[0056] In some embodiments, the positive electrode includes a fluorine-based binder having a melting point in the range of 155° C. to 270° C. In some embodiments, the melting point of the fluorine-based binder is 155° C., 160° C., 165° C., 170° C., 172° C., 175° C., 180° C., 200° C., 220° C., 220° C., 230° C., 240° C., 250° C., 260° C., 270° C., or a range consisting of any two of these values.

[0057] When using a fluorine-based binder with a melting point in the range of 155°C to 270°C, excellent DC internal resistance under high temperature and high pressure and floating charge performance under high temperature and high pressure are also obtained. In particular, when using a fluorine-based binder with a melting point in the range of 155°C to 260°C, it can be further evenly distributed on the surface of the positive electrode material particles during the baking or hot pressing process of the pole piece preparation process, effectively improving the adhesion effect, suppressing the surface defects of the pole piece, and further improving the performance of the lithium-ion battery.

[0058] In some embodiments, the fluorine-based binder includes polyvinylidene fluoride. In some embodiments, the polyvinylidene fluoride includes a homopolymer of vinylidene fluoride as a monomer and a copolymer of vinylidene fluoride (VdF) as a monomer. In some embodiments, the end of the polyvinylidene fluoride may be modified with maleic acid.

[0059] In some embodiments, based on the mass of the positive electrode active material layer, the mass percentage of the fluorine-based binder is 0.5% to 3%. In some embodiments, based on the mass of the positive electrode active material layer, the mass percentage of the fluorine-based binder is 0.5%, 0.8%, 1.0%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3%, or a range consisting of any two of these values.

[0060] When the content of the fluorine-based binder is less than 0.5%, the coverage of the positive electrode active material particles by the fluorine-based binder becomes insufficient, the bonding property decreases, and the cracking phenomenon worsens. On the other hand, when the content of the fluorine-based binder exceeds 3%, the positive electrode active material particles are excessively covered by the fluorine-based binder, resulting in an increase in DC resistance, and high discharge rate performance cannot be obtained in a low temperature environment, and good floating charge performance cannot be obtained in a high temperature environment.

[0061] (5) Additives in the positive electrode active material layer

[0062] In some embodiments, the positive electrode active material layer includes an auxiliary agent. In some embodiments, the auxiliary agent includes a polymer compound having an ether bond, wherein the mass percentage of the polymer compound having an ether bond is M4%, M4≤0.3 based on the mass of the positive electrode active material layer.

[0063] In some embodiments, M4 is 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.12, 0.14, 0.15, 0.18, 0.2, 0.25, 0.28, 0.3 or a range consisting of any two of these values. When the content of the auxiliary agent is within the above range, it helps to improve the following properties of the electrochemical device: output power characteristics, load characteristics, low temperature characteristics, cycle characteristics, and high temperature storage characteristics.

[0064] In some embodiments, the oxidation potential of the polymer compound having an ether bond is greater than or equal to 4.6 V. In some embodiments, the oxidation potential of the polymer compound having an ether bond is 4.6 V, 4.7 V, 4.8 V, 4.9 V, 5.0 V, 5.1 V, 5.2 V, 5.3 V, 5.4 V, 5.5 V, 5.6 V, 6 V, or a range consisting of any two of these values. When the oxidation potential of the additive is within the above range, the electrochemical performance of the electrochemical device is stable and resistant to high voltage, which helps to improve the floating charge performance of the electrochemical device under high temperature and high pressure.

[0065] In some embodiments, the polymer compound having an ether bond includes at least one of polyethylene oxide, polyether, polyol or polyol ester.

[0066] (6) Positive electrode active material

[0067] In some embodiments, the type of the positive electrode active material is not particularly limited, as long as it can electrochemically absorb and release metal ions (e.g., lithium ions). In some embodiments, the positive electrode active material is a material containing lithium and at least one transition metal. Examples of positive electrode active materials may include, but are not limited to, lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds.

[0068] In some embodiments, the transition metal in the lithium transition metal composite oxide includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium transition metal composite oxide includes lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2 and the like, wherein a portion of the transition metal atoms serving as the main body of these lithium transition metal composite oxides are replaced by other elements such as Na, K, B, F, Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Nb, Mo, Sn, W, etc. Examples of lithium transition metal composite oxides may include, but are not limited to, LiNi 0.5 Mn 0.5 O2、LiNi 0.85 Co 0.10 Al 0.05 O2、LiNi 0.33 Co 0.33 Mn 0.33 O2、LiNi 0.45 Co 0.10 Al 0.45 O2、LiMn 1.8 Al 0.2 O4 and LiMn 1.5 Ni 0.5 O4, etc. Examples of combinations of lithium transition metal composite oxides include, but are not limited to, combinations of LiCoO2 and LiMn2O4, wherein a portion of the Mn in LiMn2O4 may be replaced by a transition metal (e.g., LiNi 0.33 Co 0.33 Mn 0.33 O2), part of the Co in LiCoO2 can be replaced by transition metals.

[0069] In some embodiments, the transition metal in the lithium-containing transition metal phosphate compound includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium-containing transition metal phosphate compound includes iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, and cobalt phosphates such as LiCoPO4, wherein a portion of the transition metal atoms as the main body of these lithium transition metal phosphate compounds are replaced by other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.

[0070] In some embodiments, the positive electrode active material includes lithium phosphate, which can improve the continuous charging characteristics of the electrochemical device. There is no limitation on the use of lithium phosphate. In some embodiments, the positive electrode active material and lithium phosphate are mixed. In some embodiments, the mass percentage of lithium phosphate is greater than 0.1%, greater than 0.3% or greater than 0.5% relative to the mass of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the mass percentage of lithium phosphate is less than 10%, less than 8% or less than 5% relative to the mass of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is within the range formed by any two of the above-mentioned values.

[0071] A substance having a different composition from that of the positive electrode active material may be attached to the surface of the positive electrode active material. Examples of the surface-attached substance may include, but are not limited to: oxides such as aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and carbon.

[0072] These surface-attached substances can be attached to the surface of the positive electrode active material by the following methods: a method in which the surface-attached substance is dissolved or suspended in a solvent, infiltrated into the positive electrode active material, and then dried; a method in which a surface-attached substance precursor is dissolved or suspended in a solvent, infiltrated into the positive electrode active material, and then reacted by heating or the like; and a method in which the surface-attached substance is added to the positive electrode active material precursor and then fired simultaneously, etc. In the case of carbon attachment, a method in which a carbon material (e.g., activated carbon, etc.) is mechanically attached can also be used.

[0073] In some embodiments, based on the mass of the positive electrode active material layer, the content of the surface-attached substance is greater than 0.1 ppm, greater than 1 ppm, or greater than 10 ppm. In some embodiments, based on the mass of the positive electrode active material layer, the content of the surface-attached substance is less than 10%, less than 5%, or less than 2%. In some embodiments, based on the mass of the positive electrode active material layer, the content of the surface-attached substance is within the range formed by any two of the above values.

[0074] By attaching substances to the surface of the positive electrode active material, the oxidation reaction of the electrolyte on the surface of the positive electrode active material can be suppressed, and the life of the electrochemical device can be improved. When the amount of surface-attached substances is too small, the effect cannot be fully demonstrated; when the amount of surface-attached substances is too large, it will hinder the entry and exit of lithium ions, and the resistance may sometimes increase.

[0075] In the present application, a positive electrode active material in which a substance having a composition different from that of the positive electrode active material is attached to the surface of the positive electrode active material is also referred to as a “positive electrode active material”.

[0076] In some embodiments, the shape of the positive electrode active material particles includes, but is not limited to, block, polyhedron, sphere, ellipsoid, plate, needle and column, etc. In some embodiments, the positive electrode active material particles include primary particles, secondary particles or a combination thereof. In some embodiments, the primary particles can be agglomerated to form secondary particles.

[0077] In some embodiments, the tap density of the positive electrode active material is greater than 0.5 g / cm 3 , greater than 0.8 g / cm 3 or greater than 1.0 g / cm 3 . When the tap density of the positive electrode active material is within the above range, the amount of dispersion medium and the required amount of conductive material and positive electrode binder required for the formation of the positive electrode active material layer can be suppressed, thereby ensuring the filling rate of the positive electrode active material and the capacity of the electrochemical device. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density, the better, and there is no particular upper limit. In some embodiments, the tap density of the positive electrode active material is less than 4.0 g / cm 3 , less than 3.7 g / cm 3 or less than 3.5 g / cm 3 When the tap density of the positive electrode active material has the upper limit as described above, a decrease in load characteristics can be suppressed.

[0078] The tap density of the positive electrode active material can be calculated as follows: 5 g to 10 g of the positive electrode active material powder is placed in a 10 mL glass measuring cylinder and vibrated 200 times with a stroke of 20 mm to obtain the powder packing density (tap density).

[0079] When the positive electrode active material particles are primary particles, the median particle size (D50) of the positive electrode active material particles refers to the primary particle size of the positive electrode active material particles. When the primary particles of the positive electrode active material particles aggregate to form secondary particles, the median particle size (D50) of the positive electrode active material particles refers to the secondary particle size of the positive electrode active material particles.

[0080] In some embodiments, the median particle size (D50) of the positive electrode active material particles is greater than 0.3 μm, greater than 0.5 μm, greater than 0.8 μm, or greater than 1.0 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is less than 30 μm, less than 27 μm, less than 25 μm, or less than 22 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is within the range composed of any two of the above values. When the median particle size (D50) of the positive electrode active material particles is within the above range, a positive electrode active material with a high tap density can be obtained, which can suppress the reduction in the performance of the electrochemical device. On the other hand, in the preparation process of the positive electrode of the electrochemical device (that is, when the positive electrode active material, the conductive material, and the binder are slurried with a solvent and coated in a thin film), problems such as streaks can be prevented. Here, by mixing two or more positive electrode active materials with different median particle sizes, the filling property during the preparation of the positive electrode can be further improved.

[0081] The median particle size (D50) of the positive electrode active material particles can be measured using a laser diffraction / scattering particle size distribution measuring device: when using LA-920 manufactured by HORIBA as a particle size distribution meter, a 0.1% sodium hexametaphosphate aqueous solution is used as the dispersion medium used in the measurement, and the measurement refractive index is set to 1.24 after 5 minutes of ultrasonic dispersion.

[0082] In some embodiments, the positive electrode active material satisfies one of the following conditions:

[0083] (1) The positive electrode active material includes lithium iron phosphate, and the D50 of the positive electrode active material is D1µm, where 2×D1≥W;

[0084] (2) The positive electrode active material includes lithium manganese iron phosphate, and the D50 of the positive electrode active material is D2μm, where 5×D2≥W;

[0085] (3) The positive electrode active material includes lithium manganate, and the D50 of the positive electrode active material is D3µm, where 0.1×D3≥W;

[0086] (4) the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the D50 of the positive electrode active material is D4 μm, wherein 0.15×D4≥W; and

[0087] (5) The positive electrode active material includes lithium cobalt oxide, and D50 of the positive electrode active material is D5µm, where 0.15×D5≥W.

[0088] In some embodiments, the above-mentioned positive electrode active materials such as lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium cobalt oxide can be used alone or in any combination. By selecting a suitable particle size, the flatness of the positive electrode surface and the compaction density of the electrode can be further adjusted, thereby improving the performance of the lithium-ion battery.

[0089] In some embodiments, the positive electrode active material layer further includes a conductive agent. In some embodiments, the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black, or carbon black.

[0090] In some embodiments, the positive electrode current collector includes at least one of copper foil or aluminum foil.

[0091] In some embodiments, the positive electrode can be prepared by a preparation method known in the art. For example, the positive electrode can be obtained by mixing a positive electrode active material, a conductive agent, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include N-methylpyrrolidone, etc., but is not limited thereto.

[0092] 2. Electrolyte

[0093] In some embodiments, the electrolyte used in the electrochemical device of the present application includes an electrolyte and a solvent for dissolving the electrolyte. In some embodiments, the electrolyte includes an additive A, and the additive A includes at least one of a compound having a cyano group or a compound having a FPO bond.

[0094] When a compound having a cyano group or a compound having an FPO bond is added to the electrolyte, excellent DC internal resistance under high temperature and high pressure and floating charge performance under high temperature and high pressure can be obtained. In particular, when a compound having a cyano group and a compound having an FPO bond are used in combination, the surface defects of the electrode sheet caused by the decomposition and reconstruction of the positive electrode surface protective film during the cycle can be further suppressed, thereby improving the performance of the lithium-ion battery.

[0095] In some embodiments, the mass percentage of the additive A is a%, and the value of a ranges from 0.1 to 15. In some embodiments, a is 0.1, 0.4, 0.5, 0.8, 1, 1.5, 1.8, 2, 2.5, 3, 3.5, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of these values.

[0096] In some embodiments, M / a is 6.33, 8, 10, 15, 20, 24, 28, 30, 32, 35, 40, 45, 50, 100, 150, 190, 200, 250 or a range consisting of any two of these values. When the above relationship is satisfied, the consistency of the pole piece surface is well maintained during the cycle, so not only the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure are further improved, but also unexpectedly, the capacity retention rate under high voltage and the rate performance under low temperature are improved at the same time, which may be due to the good stability and low impedance of the interface formed between the positive electrode and the electrolyte under high pressure and low temperature, which can make lithium ions easier to deintercalate.

[0097] In some embodiments, the compound having a cyano group includes at least one of the following compounds: succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether , 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol di(2-cyanoethyl)ether, triethylene glycol di(2-cyanoethyl)ether, tetraethylene glycol di(2-cyanoethyl)ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl)ether, 1,4-dicyano-2-butene, 1 ,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexatriconitrile, 1,2,6-hexatriconitrile , 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane or 1,2,5-tris(cyanoethoxy)pentane.

[0098] In some embodiments, the compound having a FPO bond includes at least one of lithium difluorophosphate, a compound of Formula 1, a compound of Formula 2, a compound of Formula 3, or a compound of Formula 4: Formula 1, Formula 2: Formula 3, Formula 4.

[0099] In some embodiments, the electrolyte further includes an additive B, and the additive B includes at least one of fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate, vinyl ethylene carbonate, and phosphoric acid cyclic anhydride.

[0100] In some embodiments, the electrolyte further comprises any non-aqueous solvent known in the prior art that can be used as a solvent for the electrolyte.

[0101] In some embodiments, the non-aqueous solvent includes, but is not limited to, one or more of the following: cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.

[0102] In some embodiments, examples of the cyclic carbonate may include, but are not limited to, one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate. In some embodiments, the cyclic carbonate has 3-6 carbon atoms.

[0103] In some embodiments, examples of the chain carbonates may include, but are not limited to, one or more of the following: dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate, etc. Examples of chain carbonates substituted with fluorine may include, but are not limited to, one or more of the following: bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate, and 2,2,2-trifluoroethyl methyl carbonate, etc.

[0104] In some embodiments, examples of the cyclic carboxylic acid ester may include, but are not limited to, one or more of the following: one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.

[0105] In some embodiments, examples of the chain carboxylic acid esters may include, but are not limited to, one or more of the following: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate, etc. In some embodiments, some hydrogen atoms of the chain carboxylic acid ester may be substituted by fluorine. In some embodiments, examples of fluorine-substituted chain carboxylic acid esters may include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate, etc.

[0106] In some embodiments, examples of the cyclic ether may include, but are not limited to, one or more of the following: tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl1,3-dioxolane, 4-methyl1,3-dioxolane, 1,3-dioxane, 1,4-dioxane and dimethoxypropane.

[0107] In some embodiments, examples of the chain ether may include, but are not limited to, one or more of the following: dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane and 1,2-ethoxymethoxyethane, etc.

[0108] In some embodiments, examples of the phosphorus-containing organic solvent may include, but are not limited to, one or more of the following: trimethyl phosphate, triethyl phosphate, dimethyl ethyl phosphate, diethyl methyl phosphate, ethylidene methyl phosphate, ethylidene ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphate, and tris(2,2,3,3,3-pentafluoropropyl) phosphate, etc.

[0109] In some embodiments, examples of the sulfur-containing organic solvent may include, but are not limited to, one or more of the following: sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be substituted by fluorine.

[0110] In some embodiments, the aromatic fluorine-containing solvent includes, but is not limited to, one or more of the following: fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.

[0111] In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes an organic solvent selected from the group consisting of the following substances: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.

[0112] In some embodiments, the electrolyte is not particularly limited, and any substance known as an electrolyte can be used arbitrarily. In the case of a lithium secondary battery, a lithium salt is generally used. Examples of electrolytes may include, but are not limited to, inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, LiWF7; lithium tungstates such as LiWOF5; lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, CF3CF2CF2CF2CO2Li; lithium salts such as FSO3Li, CH3SO3Li 、CH2FSO3Li、CHF2SO3Li、CF3SO3Li、CF3CF2SO3Li、CF3CF2CF2SO3Li、CF3CF2CF2CF2SO3Li and other lithium sulfonate salts; LiN(FCO)2、LiN(FCO)(FSO2)、LiN(FSO2)2、LiN(FSO2)(CF3SO2)、LiN(CF3SO2)2、LiN(C2F5SO2)2、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide Lithium, LiN(CF3SO2)(C4F9SO2) and other imide lithium salts; LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3 and other methylated lithium salts; (malonate) borate lithium salts such as bis(malonate) borate and difluoro(malonate) borate lithium salts; (malonate) phosphate lithium salts such as tris(malonate) phosphate, difluorobis(malonate) phosphate, tetrafluoro(malonate) phosphate; and LiPF4(CF3)2, LiPF4(C2F5)2, Fluorine-containing organic lithium salts such as LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium oxalate borate salts such as lithium difluorooxalatoborate and lithium bis(oxalato)borate; lithium oxalate phosphate salts such as lithium tetrafluorooxalato phosphate, lithium difluorobis(oxalato) phosphate and lithium tris(oxalato) phosphate, etc.

[0113] In some embodiments, the electrolyte is selected from LiPF6, LiSbF6, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, lithium difluorooxalatoborate, lithium bis(oxalate)borate or lithium difluorobis(oxalato)phosphate, which helps to improve the output power characteristics, high-rate charge and discharge characteristics, high-temperature storage characteristics and cycle characteristics of the electrochemical device.

[0114] The content of the electrolyte is not particularly limited as long as it does not impair the effect of the present application. In some embodiments, the total molar concentration of lithium in the electrolyte is greater than 0.3 mol / L, greater than 0.4 mol / L or greater than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within the range formed by any two of the above values. When the electrolyte concentration is within the above range, the lithium as a charged particle will not be too little, and the viscosity can be kept in an appropriate range, thereby easily ensuring good conductivity.

[0115] When two or more electrolytes are used, the electrolyte includes at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a salt selected from the group consisting of monofluorophosphate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a lithium salt. In some embodiments, based on the mass of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is greater than 0.01% or greater than 0.1%. In some embodiments, based on the mass of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is less than 20% or less than 10%. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is within the range of any two of the above values.

[0116] In some embodiments, the electrolyte comprises one or more substances selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate and one or more other salts. As other salts, the lithium salts exemplified above can be cited, and in some embodiments, they are LiPF6, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3. In some embodiments, the salt other than this is LiPF6.

[0117] In some embodiments, the content of other salts is greater than 0.01% or greater than 0.1% based on the mass of the electrolyte. In some embodiments, the content of other salts is less than 20%, less than 15% or less than 10% based on the mass of the electrolyte. In some embodiments, the content of other salts is within the range formed by any two of the above values. Other salts having the above content help balance the conductivity and viscosity of the electrolyte.

[0118] 3. Negative electrode

[0119] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on one or both surfaces of the negative electrode current collector. The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer can be one or more layers, and each layer of the multilayer negative electrode active material can contain the same or different negative electrode active materials. The negative electrode active material is any material that can reversibly embed and deintercalate metal ions such as lithium ions. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the negative electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0120] As a current collector for holding the negative electrode active material, any known current collector can be used. Examples of negative electrode current collectors include, but are not limited to, metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.

[0121] In the case where the negative electrode current collector is a metal material, the negative electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip, metal plate, metal film, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the negative electrode current collector is a metal film. In some embodiments, the negative electrode current collector is a copper foil. In some embodiments, the negative electrode current collector is a rolled copper foil based on a rolling method or an electrolytic copper foil based on an electrolytic method.

[0122] In some embodiments, the thickness of the negative electrode current collector is greater than 1 μm or greater than 5 μm. In some embodiments, the thickness of the negative electrode current collector is less than 100 μm or less than 50 μm. In some embodiments, the thickness of the negative electrode current collector is within the range formed by any two of the above values.

[0123] There is no particular limitation on the negative electrode active material, as long as it can reversibly absorb and release lithium ions. Examples of negative electrode active materials may include, but are not limited to, carbon materials such as natural graphite and artificial graphite; metals such as silicon (Si) and tin (Sn); or oxides of metal elements such as Si and Sn. Negative electrode active materials may be used alone or in combination.

[0124] In some embodiments, the negative electrode active material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0125] In some embodiments, the negative electrode can be prepared by the following method: coating a negative electrode mixture slurry containing a negative electrode active material, a resin binder, etc. on a negative electrode current collector, drying it, and then rolling it to form a negative electrode active material layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.

[0126] 4. Isolation film

[0127] In some embodiments, in order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually infiltrated into the separator for use.

[0128] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.

[0129] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0130] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (eg, barium sulfate, calcium sulfate, etc.). The form of the inorganic material may include, but is not limited to, granular or fibrous.

[0131] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators can also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with alumina particles having a particle size of 90% less than 1 μm.

[0132] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the separator is within the range of any two of the above values. When the thickness of the separator is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.

[0133] When a porous material such as a porous sheet or non-woven fabric is used as an isolation membrane, the porosity of the isolation membrane is arbitrary. In some embodiments, the porosity of the isolation membrane is greater than 10%, greater than 15%, or greater than 20%. In some embodiments, the porosity of the isolation membrane is less than 60%, less than 50%, or less than 45%. In some embodiments, the porosity of the isolation membrane is within the range formed by any two of the above values. When the porosity of the isolation membrane is within the above range, insulation and mechanical strength can be ensured, and membrane resistance can be suppressed, so that the electrochemical device has good safety characteristics.

[0134] The average pore size of the isolation membrane is also arbitrary. In some embodiments, the average pore size of the isolation membrane is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the isolation membrane is greater than 0.05 μm. In some embodiments, the average pore size of the isolation membrane is within the range formed by any two of the above values. If the average pore size of the isolation membrane exceeds the above range, short circuit is likely to occur. When the average pore size of the isolation membrane is within the above range, the electrochemical device has good safety characteristics.

[0135] 5. Electrochemical device

[0136] In some embodiments, an electrochemical device includes an electrode assembly, a current collecting structure, an outer casing, and a protective element.

[0137] Electrode Group

[0138] The electrode group may be any one of a stacked structure formed by stacking the positive electrode and the negative electrode with the separator interposed therebetween, and a structure formed by spirally winding the positive electrode and the negative electrode with the separator interposed therebetween. In some embodiments, the proportion of the mass of the electrode group in the internal volume of the battery (electrode group occupancy) is greater than 40% or greater than 50%. In some embodiments, the electrode group occupancy is less than 90% or less than 80%. In some embodiments, the electrode group occupancy is within the range formed by any two of the above values. When the electrode group occupancy is within the above range, the capacity of the electrochemical device can be ensured, and at the same time, the reduction in characteristics such as repeated charge and discharge performance and high temperature storage associated with the increase in internal pressure can be suppressed.

[0139] Current collection structure

[0140] There is no particular limitation on the current collection structure. In some embodiments, the current collection structure is a structure that reduces the resistance of the wiring portion and the joint portion. When the electrode group is the above-mentioned stacked structure, it is suitable to use a structure formed by bundling the metal core portions of each electrode layer and welding them to the terminal. When the electrode area of ​​a sheet increases, the internal resistance increases, so it is also suitable to set more than two terminals in the electrode to reduce the resistance. When the electrode group is the above-mentioned winding structure, the internal resistance can be reduced by setting more than two lead structures at the positive electrode and the negative electrode respectively, and bundling them at the terminal.

[0141] External shell

[0142] The material of the outer casing is not particularly limited, as long as it is a material that is stable to the electrolyte used. The outer casing can be made of, but not limited to, nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy and other metals, or a laminated film of resin and aluminum foil. In some embodiments, the outer casing is a metal or laminated film of aluminum or aluminum alloy.

[0143] The metal outer casing includes, but is not limited to, a packaged closed structure formed by welding metals to each other by laser welding, resistance welding, and ultrasonic welding; or a riveted structure formed by using the above-mentioned metals through a resin gasket. The outer casing using the above-mentioned laminated film includes, but is not limited to, a packaged closed structure formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above-mentioned resin layers. When the resin layer is thermally bonded to form a closed structure through the collector terminal, due to the bonding between the metal and the resin, a resin with a polar group or a modified resin into which a polar group is introduced can be used as the sandwiched resin. In addition, the shape of the outer casing is also arbitrary, for example, it can be any of cylindrical, square, laminated, button-shaped, large, etc.

[0144] Protection components

[0145] The protective element may be a positive temperature coefficient (PTC) whose resistance increases when abnormal heat generation or excessive current flows, a temperature fuse, a thermistor, or a valve (current cutoff valve) that cuts off the current flowing in the circuit by causing the internal pressure or internal temperature of the battery to rise sharply when abnormal heat generation occurs. The above-mentioned protective element may be selected to be an element that does not operate in normal use of high current, or may be designed in a form that does not cause abnormal heat generation or thermal runaway even if the protective element is not present.

[0146] 6. Application

[0147] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery or a lithium ion secondary battery.

[0148] The present application further provides an electronic device, which includes the electrochemical device according to the present application.

[0149] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0150] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.

[0151] Example

[0152] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.

[0153] 1. Preparation of lithium-ion batteries

[0154] 1. Preparation of negative electrode

[0155] Artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed with deionized water in a mass ratio of 96%:2%:2%, and stirred evenly to obtain a slurry. The slurry was coated on a 9μm copper foil. After drying, cold pressing, cutting and welding of the tabs, a negative electrode was obtained.

[0156] 2. Preparation of positive electrode

[0157] The positive electrode active material (such as lithium cobalt oxide), Super-P and polyvinylidene fluoride are mixed with N-methylpyrrolidone (NMP) in a mass ratio of (95-99%): (0.1-5%): (0.1-5%), and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on a 12 μm aluminum foil, dried, cold pressed, and then cut and welded to the tabs to obtain the positive electrode.

[0158] 3. Preparation of electrolyte

[0159] In a dry argon environment, EC, PP and DEC (mass ratio 1:1:1) were mixed, and LiPF6 was added and mixed evenly to form a basic electrolyte, in which the content of LiPF6 was 12%. Different amounts of additives were added to the basic electrolyte to obtain electrolytes of different embodiments and comparative examples. The mass percentage of each substance in the electrolyte was calculated based on the total mass of the electrolyte.

[0160] The abbreviations and names of the components in the electrolyte are shown in the following table:

[0161] 4. Preparation of isolation membrane

[0162] A polyethylene porous membrane with an aluminum oxide coating was used as the separator with a thickness of 9 µm.

[0163] 5. Preparation of lithium-ion batteries

[0164] The obtained positive electrode, separator and negative electrode are wound in order and placed in an outer packaging foil, leaving a liquid injection port. The electrolyte is poured from the liquid injection port, packaged, and then subjected to formation, capacity and other processes to obtain a lithium-ion battery.

[0165] 2. Test Method

[0166] 1. Test method of DC internal resistance of lithium-ion battery under high temperature and high pressure

[0167] At 65°C, charge the lithium-ion battery to 4.7V at 1.5C constant current, then charge to 0.05C at 4.7V constant voltage, and let it stand for 30 minutes. Discharge at 0.1C for 10 seconds, record the voltage value as U1, discharge at 1C for 360 seconds, record the voltage value as U2. Repeat the charge and discharge steps 5 times. "1C" is the current value that completely discharges the capacity of the lithium-ion battery within 1 hour.

[0168] The DC resistance R of a lithium-ion battery at 65°C is calculated by the following formula:

[0169] R=(U2-U1) / (1C-0.1C).

[0170] 2. Test method for floating charge performance of lithium-ion batteries under high temperature and high pressure

[0171] At 25°C, the lithium-ion battery was discharged at 0.5C to 4.7V, then charged at 0.5C to 4.7V, and then charged at a constant voltage of 0.05C at 4.7V. It was placed in a 50°C oven and charged at a constant voltage of 4.7V with a cutoff current of 20mA to monitor the change in the thickness of the lithium-ion battery. The thickness at the initial 50% state of charge (State of Charge, SOC) was used as the benchmark, and the increase in battery thickness by more than 20% was considered the failure point, and the floating charge time to reach the failure point was recorded.

[0172] 3. Test method for capacity retention of lithium-ion batteries under high temperature and high pressure

[0173] At 45°C, the lithium-ion battery is charged to 4.7V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage, and then discharged to 3.0V at a constant current of 1C. This is the first cycle. The lithium-ion battery is cycled 800 times under the above conditions. The capacity retention rate after the cycle is calculated according to the following formula:

[0174] Capacity retention rate = (discharge capacity after 800 cycles / discharge capacity of the first cycle) × 100%.

[0175] 4. Test method for low temperature discharge performance of lithium-ion batteries

[0176] At 25°C, charge at 0.5C constant current to 4.7V, charge at constant voltage to 0.05C cut-off, then discharge at 0.5C constant current to 3.0V cut-off, record as 25°C discharge capacity. At 25°C, charge at 0.5C constant current to 4.7V, charge at constant voltage to 0.05C cut-off, then place the battery in a -20°C constant temperature box, let stand for 2 hours, then discharge at 0.5C constant current to 3.0V cut-off, record as -20°C discharge capacity. Calculate the discharge percentage of lithium-ion batteries by the following formula:

[0177] Discharge percentage = [-20℃ discharge capacity / 25℃ discharge capacity] × 100%.

[0178] 5. Test method for crack width

[0179] Take the positive electrode plate disassembled from the battery, cut the plate into a 40mm (width) × 100mm (length) rectangular sample with a knife along the crack direction, and then clamp the sample with two 2mm (thickness) × 70mm (width) × 140mm (length) smooth and clean glass plates to make a sample. Place the front side of the sample crack on the stage of the KEYENCE VHX-5000 optical microscope, observe and take pictures at 100× magnification. Then use the VHX-5000 software to measure the width of the widest part of the crack using the parallel line method (select the two adjacent widest points to form a straight line), measure each crack 5 times, and take the maximum value as the crack width, that is, W mm.

[0180] 6. Testing method for melting point of fluorine-based adhesive

[0181] The melting point of the fluorine-based binder can be determined by the following operation: First, remove the positive electrode from the battery, wash it with dimethyl carbonate, dry it, remove the current collector, heat and stir it in an appropriate dispersion medium (such as N-methylpyrrolidone, etc.), so that the binder is dissolved in the dispersion medium. After that, the positive electrode active material is removed by centrifugation, and after filtering the supernatant, the binder can be removed by evaporation or reprecipitation in water. Secondly, using a differential scanning calorimeter (DSC, such as Rigaku Thermo plusDSC8230 manufactured by Rigaku Corporation), a few mg to tens of mg of the sample is heated at a heating rate of 1 to 10°C / min, and the temperature representing the maximum endothermic heat in the endothermic peak appearing in the temperature range of 100°C to 300°C is set as the melting point of the fluorine-based binder.

[0182] 7. Test method for the content of fluorine-based binder

[0183] The content of the fluorine-based binder is determined by the following operation: First, the positive electrode is taken out from the battery, washed with dimethyl carbonate and dried. Then, a differential thermal balance device (TG-DTA, such as Rigaku Thermo plus TG8120 manufactured by Rigaku Corporation) is used to heat several mg to tens of mg of the sample at a heating rate of 1 to 5 ° C / min in an air atmosphere to 600 ° C, and the content of the fluorine-based binder in the positive electrode active material layer is obtained according to the mass reduction at this time. It should be noted that whether the mass reduction is caused by the binder, the operation is described as described using the above-mentioned method for determining the melting point of the binder, the binder is separated, and the TG-DTA measurement of the binder alone is performed in an air atmosphere, and it can be confirmed by investigating how much the binder burns.

[0184] 3. Test Results

[0185] A. Table 1 shows the influence of the mass percentage (M%) of the positive electrode active material in the positive electrode active material layer and the crack width (Wmm) on the surface of the positive electrode active material layer on the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure of the lithium-ion battery. The positive electrode material in Table 1 is Hunan Shanshan lithium cobalt oxide LC9000E; the electrolyte is the basic electrolyte. The difference between Examples 1-2 to 1-13 and Comparative Examples 1-1 to 1-3 and Example 1-1 is only the parameters listed in Table 1, and the other parameters are the same.

[0186] Table 1

[0187] It can be seen from the above test results that when the mass fraction of the positive electrode active material is 95% to 99%, and the positive electrode satisfies M / W ≥ 47.5, the DC internal resistance of the lithium-ion battery under high temperature and high pressure and the floating charge performance under high temperature and high pressure are significantly improved. Specifically, the higher the mass fraction of the positive electrode active material, the more conducive to the improvement of the battery energy density. However, when the mass fraction of the positive electrode active material exceeds 99%, the proportion of the corresponding binder and conductive agent will decrease, making the electrode processing difficult and causing obvious cracking. When W ≤ 2, the ionic conductivity and electronic conductivity of the positive electrode surface and interior can be improved, so a lower DC internal resistance can be obtained, and the performance of the electrochemical device is better. Once the crack width of the electrode is large, for example, more than 2 mm, it will have a serious impact on the ionic conductivity and electronic conductivity, causing the battery performance to deteriorate.

[0188] By controlling M and M / W within a suitable range, the present application can reduce defects on the positive electrode surface such as cracks, pits, craters, pinholes, etc., effectively inhibit the continuous destruction of the passivation layer on the positive electrode surface during the battery charge and discharge cycle, reduce the number of repairs, so that lithium ions obtain a smooth deintercalation channel, and reduce the SOC unevenness on the electrode surface (that is, the accumulation of charge carriers at defects), because the place where SOC unevenness occurs is often the starting point of electrode degradation.

[0189] Figure 1 The SEM images of the surface of the positive electrode active material layer in Examples 1 to 8 of the present application are shown. The images show that the surface of the positive electrode active material layer has a crack width of 0.3 mm.

[0190] B. Table 2 shows the mass per unit area of ​​the positive electrode active material layer (M1 mg / 1540.25 mm 2 ) and the crack width (Wmm) of the positive electrode active material layer surface on the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure of the lithium ion battery. The difference between Examples 2-1 to 2-15 and Example 1-1 is only the parameters listed in Table 2.

[0191] Table 2

[0192] It can be seen from the above test results that when M1 ranges from 100 to 400 and satisfies M1 / W≥50, the positive electrode surface can maintain structural stability during the charge and discharge cycle, further reducing the DC internal resistance of the lithium-ion battery and improving its floating charge performance.

[0193] C. Table 3 shows the effects of the solid content (M2%) of the positive electrode active material layer coating slurry and the crack width (Wmm) on the surface of the positive electrode active material layer on the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure of the lithium ion battery. The difference between Examples 3-1 to 3-15 and Example 1-1 is only the parameters listed in Table 3.

[0194] Table 3

[0195] It can be seen from the above test results that when the solid content of the positive electrode active material layer coating slurry is 55% to 80% and satisfies M2 / W≥27.5, the positive electrode surface defects are relatively small, which further reduces the DC internal resistance of the lithium-ion battery and improves the floating charge performance of the lithium-ion battery.

[0196] D. Table 4-1 shows the influence of the melting point of the positive electrode binder on the DC internal resistance and floating charge performance of the lithium-ion battery under high temperature and high pressure. The difference between Examples 4-1 to 4-12 and Example 1-1 is only the parameters listed in Table 4-1.

[0197] Table 4-1

[0198] From the above test results, it can be seen that when using a fluorine-based binder with a melting point in the range of 155°C to 270°C, the DC internal resistance of the lithium-ion battery is further reduced and the floating charge performance of the lithium-ion battery is improved. The reason may be that when using a fluorine-based binder with a melting point in the range of 155°C to 270°C, the binder can be evenly distributed on the surface of the positive electrode material particles during the baking or hot pressing process of the pole piece preparation process, effectively improving the adhesion effect, suppressing the surface defects of the pole piece, and further improving the performance of the lithium-ion battery.

[0199] E. Table 4-2 shows the effects of the type and mass percentage (M4%) of the positive electrode additive on the DC internal resistance and floating charge performance of lithium-ion batteries under high temperature and high pressure. The difference between Examples 4-13 to 4-21 and Example 1-1 is only the parameters listed in Table 4-2. The preparation method of the positive electrode in Examples 4-13 to 4-21 is as follows: lithium cobalt oxide (Hunan Shanshan LC9000E), Super-P and polyvinylidene fluoride are mixed with N-methylpyrrolidone in a mass ratio of 95%:2%:3%, and then the additives in Table 4-2 are added to the slurry, stirred evenly, and a positive electrode slurry is obtained. The positive electrode slurry is coated on a 12 μm aluminum foil, dried, cold pressed, and then cut and welded to the pole ears to obtain a positive electrode.

[0200] Table 4-2

[0201] It can be seen from the above test results that when 0.1%-0.3% of a polymer compound with an ether bond is added to the positive electrode slurry, excellent DC internal resistance under high temperature and high pressure and floating charge performance under high temperature and high pressure are obtained. In particular, when the oxidation potential of the polymer compound with an ether bond is higher than 4.6V, the DC internal resistance of the lithium-ion battery is further reduced and the floating charge performance of the lithium-ion battery is improved. The reason may be that when a polymer compound with an ether bond is added to the positive electrode slurry, the crack width on the surface of the positive electrode active material layer can be reduced, so as to further suppress the surface defects of the pole piece and improve the performance of the lithium-ion battery under high voltage.

[0202] F. Table 5 shows the effects of the type and particle size (D50) of the positive electrode active material and the crack width on the surface of the positive electrode active material layer on the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure of the lithium ion battery. The difference between Examples 5-1 to 5-6 and Example 1-1 is only the parameters listed in Table 5.

[0203] Table 5

[0204] It can be seen from the above test results that when the particle size of the positive electrode active material and the crack width on the surface of the positive electrode active material layer meet one of the following conditions, the DC internal resistance of the lithium-ion battery is further reduced and the floating charge performance of the lithium-ion battery is improved:

[0205] (1) The positive electrode active material includes lithium iron phosphate, and the D50 of the positive electrode active material is D1µm, where 2×D1≥W;

[0206] (2) The positive electrode active material includes lithium manganese iron phosphate, and the D50 of the positive electrode active material is D2μm, where 5×D2≥W;

[0207] (3) The positive electrode active material includes lithium manganate, and the D50 of the positive electrode active material is D3µm, where 0.1×D3≥W;

[0208] (4) the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the D50 of the positive electrode active material is D4 μm, wherein 0.15×D4≥W; and

[0209] (5) The positive electrode active material includes lithium cobalt oxide, and D50 of the positive electrode active material is D5µm, where 0.15×D5≥W.

[0210] The reason may be that by selecting the appropriate particle size, the flatness of the positive electrode surface can be further adjusted, thereby improving the performance of lithium-ion batteries.

[0211] G. Table 6 shows the effects of the type or content of electrolyte additives and the mass percentage (M%) of positive electrode active materials on the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure of lithium-ion batteries, where the mass percentage of the additives is a% based on the total mass of the electrolyte. The only difference between Examples 6-1 to 6-41 and Example 1-1 is the parameters listed in Table 6.

[0212] Table 6

[0213] It can be seen from the above test results that when a compound with a cyano group or a compound with an FPO bond is added to the electrolyte, excellent DC internal resistance under high temperature and high pressure and floating charge performance under high temperature and high pressure can be obtained. In particular, when a compound with a cyano group and a compound with an FPO bond are used in combination, the surface defects of the electrode caused by the decomposition and reconstruction of the positive electrode surface protective film during the cycle can be further suppressed, thereby improving the performance of lithium-ion batteries.

[0214] More specifically, by controlling the content of additives and M / a within a suitable range, the degradation of the electrode surface caused by uneven SOC during the battery cycle can be compensated. The additive forms a stable protective film on the positive electrode surface, which is especially important for the repair of defective parts. When M / a≥6.33, the consistency of the electrode surface is well maintained during the cycle. Therefore, not only the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure are further improved, but also, unexpectedly, the capacity retention rate under high voltage and the rate performance under low temperature are improved at the same time. This may be because at high pressure and low temperature, the interface formed between the positive electrode and the electrolyte has good stability and low impedance, which can make lithium ions easier to deintercalate.

[0215] In addition, when the electrolyte also includes at least one of fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate, vinyl ethylene carbonate, and phosphoric acid cyclic anhydride, the DC internal resistance under high temperature and high pressure and the floating charge performance under high temperature and high pressure can be further improved.

[0216] References throughout the specification to "some embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0217] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. An electrochemical device comprising a positive electrode, a negative electrode and an electrolyte, The positive electrode comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material. Based on the mass of the positive electrode active material layer, the mass percentage of the positive electrode active material is M%, and the value range of M is 95 to 99. The crack width on the surface of the positive electrode active material layer is W mm, Where M and W satisfy: M / W ≥ 47.5; The electrolyte includes an additive A, and the additive A includes a compound having a cyano group, and the compound having a cyano group includes at least one of the following compounds: succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1 ,4-Dicyanobenzene, ethylene glycol bis(propionitrile) ether, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol di(2-cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl) ether, 1, 4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexatriconitrile, 1,2, 6-hexanetricarboxylate, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane or 1,2,5-tris(cyanoethoxy)pentane. The electrochemical device according to claim 1 , wherein W≤2.

3. The electrochemical device according to claim 1, wherein the mass per unit area of ​​the positive electrode active material layer is M1 mg / 1540.25 mm 2 , the value range of M1 is 100 to 400, where M1 and W satisfy: M1 / W≥50.

4. The electrochemical device according to claim 1, wherein the solid content of the positive electrode active material layer coating slurry is M2%, the value range of M2 is 55 to 80, wherein M2 and W satisfy: M2 / W≥27.

5. 5 . The electrochemical device according to claim 1 , wherein the positive electrode comprises a fluorine-based binder having a melting point in the range of 155° C. to 270° C.

6. The electrochemical device according to claim 1, wherein the positive electrode active material layer comprises a polymer compound having an ether bond, wherein the mass percentage of the polymer compound having an ether bond based on the mass of the positive electrode active material layer is M4%, and M4≤0.

3. 7 . The electrochemical device according to claim 6 , wherein the oxidation potential of the polymer compound having an ether bond is greater than or equal to 4.6 V. 8 . The electrochemical device according to claim 1 , wherein the additive A further comprises a compound having a FPO bond.

9. The electrochemical device according to claim 8, wherein the mass percentage of the additive A is a %, and the value of a ranges from 0.1 to 15.

10. The electrochemical device according to claim 9, wherein M / a ≥ 6.

33.

11. The electrochemical device according to claim 8, wherein the compound having a FPO bond comprises at least one of lithium difluorophosphate, a compound of formula 1, a compound of formula 2, a compound of formula 3 or a compound of formula 4: Formula 1, Formula 2: Formula 3, Formula 4.

12. The electrochemical device according to claim 1, wherein the positive electrode active material satisfies one of the following conditions: (1) The positive electrode active material includes lithium iron phosphate, and the D50 of the positive electrode active material is D1µm, where 2×D1≥W; (2) The positive electrode active material includes lithium manganese iron phosphate, and the D50 of the positive electrode active material is D2μm, where 5×D2≥W; (3) The positive electrode active material includes lithium manganate, and the D50 of the positive electrode active material is D3µm, where 0.1×D3≥W; (4) the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the D50 of the positive electrode active material is D4 μm, wherein 0.15×D4≥W; and (5) The positive electrode active material includes lithium cobalt oxide, and D50 of the positive electrode active material is D5µm, where 0.15×D5≥W.

13. The electrochemical device according to claim 8, wherein the electrolyte further comprises an additive B, wherein the additive B comprises at least one of fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate, vinyl ethylene carbonate, or phosphoric acid cyclic anhydride.

14. An electronic device comprising the electrochemical device according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Lithium ion battery and cathode pole piece thereof

    CN102723458A

  • Positive pole piece and electrochemical device

    CN110943223A

  • Electrochemical device and electronic device comprising same

    CN111129592A

  • Lithium ion battery

    CN111354949A

  • High-nickel ternary lithium ion battery electrolyte and ternary lithium ion battery

    CN112216862A